Case Report: Primary intracranial high-grade myofibroblastic sarcoma and literature review - He, Xiaofeng; Lv, Min; Yuan, Jin; He, Jun; Du, Xuemei; Yang, Yang; Zhang, Hong; Wen, Feng (Frontiers in Oncology, 2025)
High-grade myofibroblastic sarcoma (HGMS) is exceedingly rare and highly aggressive, with a poor prognosis. Currently, there is no consensus on its definition. Wide resection is the standard of care for most patients, but clinical data on treatment outcomes remain limited. Here, we present the first reported case of HGMS originating intracranially. Surgical excision of the tumor was performed, followed by adjuvant radiotherapy with a total dose of 60 Gy in 30 fractions. As of November 2024, the patient had achieved 24 months of recurrence-free survival. This case may provide new evidence that could be useful for the treatment of rare primary intracranial HGMS.